NOP58 induction potentiates chemoresistance of colorectal cancer cells through aerobic glycolysis as evidenced by proteomics analysis - Wang, Feifei; Yu, Bin; Yu, Quanyong; Wang, Guanglin; Li, Baokun; Guo, Ganlin; Wang, Handong; Shen, Hui; Li, Shujin; Ma, Chunling; Jia, Xianxian; Wang, Guiying; et al. (Frontiers in Pharmacology, 2023)
The majority of individuals diagnosed with advanced colorectal cancer (CRC) will ultimately acquire resistance to 5-fluorouracil(5-FU) treatment. An increasing amount of evidence indicates that aerobic glycolysis performs a significant function in the progression and resistance of CRC. Nevertheless, the fundamental mechanisms remain to be fully understood. Proteomic analysis of 5-FU resistant CRC cells was implemented to identify and determine potential difference expression protein. These proteins may exhibit resistance mechanisms that are potentially linked to the process of aerobic glycolysis. Herein, we found that nucleolar protein 58 (NOP58) has been overexpressed within two 5-FU resistant CRC cells, HCT116-5FuR and Lovo-5FuR. Meanwhile, the glycolysis rate of drugresistant cancer cells has increased. NOP58 knockdown decreased glycolysis and enhanced the sensitivity of HCT116-5FuR and Lovo-5FuR cells to 5-FU. The proteomic analysis of chemoresistance identifies a new target involved in the cellular adaption to 5-FU and therefore highlights a possible new therapeutic strategy to overcome this resistance.